BALANCE OF PROINFLAMMATORY AND ANTI INFLAMMATORY MARKERS IN ROUTINE HEMODIALYZED PATIENTS (A STUDY OF END-STAGE RENAL FAILURE PATIENTS AT THE DR. SARDJITO HOSPITAL YOGYAKARTA) - Ira Puspitawati; Purwanto A P; Lisyani B. Suromo (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Patients with End-Stage Renal Disease (ESRD) tend to have immune imbalance triggered by uremia and Hemodialysis (HD) procedures. Contact between dialysis membrane and blood will cause bio-incompatibility reactions inducing complement activation and production of Reactive Oxygen Species (ROS) as well as proinflammatory cytokines and acute phase protein such as C-Reactive Protein (CRP). Those immune response imbalances will lead to an immunocompromised condition. The objective of this study was to prove the correlation between inflammatory markers (IL-1β, IL-6 and C-reactive proteins) and its anti-inflammatory marker (IL-10) in routine hemodialyzed patients. This is a cross-sectional observational study involving 90 subjects conducted at the Hemodialysis Installation of the Dr. Sardjito Hospital. The inclusion criteria of this study were patients who underwent routine HD procedures, aged between 18 and 65 years-old, having leukocytes count and albumin level within normal limit. The exclusion criteria of this study were patients with Acute Coronary Syndrome (ACS) and malignancies. Levels of IL-1β, IL-6  and IL-10 were measured using Enzyme-Linked Immunosorbent Assay (ELISA), while CRP was measured using highly-sensitive CRP immunoturbidimetry. Statistical analysis was performed by Spearman test. This study results showed correlations between IL-1βand IL-10 (p=0.001, r=0.302), IL-6 and IL-10 (p=0.001, r=0.418) and correlation between CRP and IL-10 (p=0.005, r=0.295). There were also correlations between IL-1β and IL-6 (p=0.029, r=0.232), IL-6 and CRP (p=0.001, r=0.534), but no correlation was found between IL- 1β and CRP (p=0.431, r=0.073). All factors that trigger the secretion of proinflammatory cytokines will trigger the release of anti-inflammatory cytokines, the consequences of anti-inflammatory cytokine secretion will happen minutes after the release of inflammatory cytokines. This study showed that there were correlations between proinflammatory and anti-inflammatory cytokines. Further studies of polymorphism-related cytokines secretion are warranted.